2016
DOI: 10.1038/srep39405
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of common NFκB-iNOS pathway by chronic Thalidomide treatment improves Hepatopulmonary Syndrome and Muscle Wasting in rats with Biliary Cirrhosis

Abstract: Thalidomide can modulate the TNFα-NFκB and iNOS pathway, which involve in the pathogenesis of hepatopulmonary syndrome (HPS) and muscle wasting in cirrhosis. In bile duct ligated-cirrhotic rats, the increased circulating CD16+ (inflammatory) monocytes and its intracellular TNFα, NFκB, monocyte chemotactic protein (MCP-1) and iNOS levels were associated with increased circulating MCP-1/soluable intercellular cell adehesion molecule-1 (sICAM-1), pulmonary TNFα/NOx, up-regulated M1 polarization, exacerbated angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…In the present study, rats subjected to Gal showed a significant elevation in the renal and hepatic contents of NOx besides iNOS activity. These results are consistent with prior studies [ 29 , 42 , 44 - 46 ]. Previous findings have shown that NO, a potent vasodilator, plays an important role in the development of hyperdynamic syndrome and peripheral vasodilation during cirrhosis [ 3 ].…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, rats subjected to Gal showed a significant elevation in the renal and hepatic contents of NOx besides iNOS activity. These results are consistent with prior studies [ 29 , 42 , 44 - 46 ]. Previous findings have shown that NO, a potent vasodilator, plays an important role in the development of hyperdynamic syndrome and peripheral vasodilation during cirrhosis [ 3 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, another study reports that BACE1 −/− mice have enhanced insulin sensitivity [ 177 ]. Notably, hyperglycaemia increases BACE1-mediated production of Aβ [ 142 ], indicative of a potentially vicious cycle between amyloid and glucose dysregulation. This also highlights the likely contribution of diseases such as diabetes mellitus to AD development and emphasises the potential of nutritional intervention strategies as a means of treating and preventing AD.…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…Then, fusion indices and myotube diameters were compared among different pretreatment groups. 27 Protein and mrnA levels in cultured c2c12 cells Then, various proteins and mRNAs of oxidative stress, autophagic, apoptotic, and lipolytic markers in cell lysates were measured with antibodies purchased from R&D Systems (Minneapolis, USA), Abcam (Cambridge, MA, USA), or Santa Cruz (Biotechnology, CA, USA) and various primers (table 1). TG content in cell lysates was measured by a TG Colorimetric assay kit (Cayman Chemical Company, Ann Arbor, MI, USA).…”
Section: Direct Effects Of Resveratrol On Palmitate-pretreated C2c12 mentioning
confidence: 99%